ANALYSIS OF REGIONAL TOURISM DEVELOPMENT STRATEGY (CASE STUDY OF LOVE BAY TOURISM IN PAYANGAN BEACH, JEMBER REGENCY) - Dini Nafisatul Mutmainah; Sekar Ayu Wulandari; Septine Brilliyantina; Inaya Rahmasari; Rahma Dita Widya Astuti (Journal of Agri Socio Economics and Business, 2022)
This study aims to develop a strategy for developing the tourism sector in Jember Regency, namely Love Bay in Payangan Beach. The method in this study uses a qualitative descriptive approach. The information was derived from primary data gradually gathered from respondents per the study’s requirements. The data collection methods used in the study were an observation carried out by entering the Love Bay tourism area on Payangan Beach and an interview conducted by asking directly to respondents who had been chosen intentionally. The results of this study are that the existence of good infrastructures, such as roads and street lighting (E2), is a sub-element that has the highest level of power effect (Driver Power) and Independence Power. On the other hand, the sub-element of easy access to tourist attractions (E1) has the lowest Driver Power and Independence. The result indicates that E1 can be influenced but cannot affects, whereas E2 can affect but is hard to influence. The conclusion that can be reached is that E2 is a sub-element with a high ability to improve the quality of regional tourism, especially Love Bay tourism, in Payangan beach, Jember Regency.